2004
DOI: 10.1002/art.20012
|View full text |Cite
|
Sign up to set email alerts
|

Detection of major histocompatibility complex/human cartilage gp‐39 complexes in rheumatoid arthritis synovitis as a specific and independent histologic marker

Abstract: Clinically, there were no correlations between mAb 12A staining and clinical or biologic parameters in RA. However, positive staining was observed in 61.5% of the inflamed RA synovial samples compared with only 3.0% of the control samples (P < 0.001). This mAb 12A staining was not related to intracellular citrullinated peptides, which are another specific histologic marker for RA.Conclusion. Presentation by synovial dendritic cells of the immunodominant epitope of HC gp-39, in the context of the shared epitope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
67
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 29 publications
10
67
0
Order By: Relevance
“…These enhanced local levels of HC gp-39 or MIA were not RA specific but were found to correlate more generally with arthritic disorders, since comparable levels were found in SF and ST of patients with spondylarthritis and osteoarthritis (ref. 19 and present study).…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…These enhanced local levels of HC gp-39 or MIA were not RA specific but were found to correlate more generally with arthritic disorders, since comparable levels were found in SF and ST of patients with spondylarthritis and osteoarthritis (ref. 19 and present study).…”
Section: Discussionsupporting
confidence: 68%
“…Previously we demonstrated that HC gp-39 is not expressed exclusively in articular cartilage but is found also in inflamed synovium and that the synovial membrane is a privileged site for presentation of this protein to the immune system (6,14,19). In immunohistochemistry analyses for MIA in the present study, collected biopsies described previously (14,19,29,33) were used to investigate local expression of MIA in the synovium, with mAb 14A.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations